2020
DOI: 10.3389/fneur.2019.01319
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of Auditory Comprehension After Theta Burst Stimulation of Wernicke's Area in Stroke Patients: A Pilot Study

Abstract: Introduction: Single-pulse transcranial magnetic stimulation (TMS) and high-frequency repetitive TMS (rTMS) over Wernicke's area were found to facilitate language functions in right-handed healthy subjects. We aimed at investigating the effects of excitatory rTMS, given as intermittent theta burst stimulation (iTBS) over left Wernicke's area, on auditory comprehension in patients suffering from fluent aphasia after stroke of the left temporal lobe. Methods: We studied 13 patients with chronic fluent aphasia af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, iTBS can modulate cortical excitability and may serve as a potential tool for neuroplasticity of impaired motor, language, and cognition brain areas [ 48 , 49 , 50 , 51 ]. This study focused on immediate effects and changes of brain activity in patients with PSA, modulated by iTBS.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, iTBS can modulate cortical excitability and may serve as a potential tool for neuroplasticity of impaired motor, language, and cognition brain areas [ 48 , 49 , 50 , 51 ]. This study focused on immediate effects and changes of brain activity in patients with PSA, modulated by iTBS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, significant activations of the left and right temporal gyrus, left posterior cingulate gyrus, and left thalamus during a language task following rTMS over the pSTG were observed by functional magnetic resonance imaging (fMRI; Kawamura et al, 2019 ). A pilot study by Versace demonstrated that excitatory intermittent TBS (iTBS) over Wernicke’s area led to transient facilitation of auditory comprehension in patients with chronic fluent aphasia ( Versace et al, 2019 ). However, these studies have several limitations, including the lack of exploration of underlying mechanisms and insufficient sample size.…”
Section: Introductionmentioning
confidence: 99%